Upper echelons and portfolio strategies of venture capital firms - Patzelt, Holger; zu Knyphausen-Aufseß, Dodo; Fischer, Heiko T. (Journal of Business Venturing, 2009)
In this study we analyze how the composition of the top management team (TMT) influences the portfolio strategy choice in venture capital (VC) organizations. We develop a model of risk perception to investigate how education and experience of TMT members impact whether VC organizations invest with a focus on early stage ventures or not, specialize or diversify across industries, and invest with a broad or narrow geographic scope. Evaluation of data on TMTs and portfolio strategies of 136 European VC firms revealed that VC firms with higher proportions of TMT members with science/engineering education and entrepreneurial experience more likely invest with an early stage focus. Furthermore, TMTs with more management education diversify their portfolios more across industries. Finally, the more international experience TMT members of VC organizations have, the broader the geographic scope of investees. We discuss the implications of our findings for the VC literature.